Capital Adjustment and the Optimal Fuel Choice - Hyland, Marie (World Bank, Washington, DC, 2016)
This paper analyzes the important, yet often ignored, link between capital adjustment and the choice of fuels used by manufacturing firms. A novel econometric framework, which explicitly incorporates heterogeneous fuel-using capital stocks in the estimation of optimal fuel choice, is applied to a large panel of Irish manufacturing firms. The econometric estimates show a significant variation in the optimal response of capital to changing fuel prices across different fuel-using technologies. For all the technologies, significant costs to capital adjustment are found. The costs are much larger compared with earlier estimates of adjustment costs based on lagged values of output and fuel prices. The findings imply that the path to full adjustment of capital stocks in response to changing fuel prices may be much longer than was previously thought.